Evaluasi Beberapa Sifat Biologi Tanah di Rhizosfer Jagung pada Lahan Terkena Tsunami Akibat Inokulasi Cendawan Mikoriza Arbuskula (CMA) dan Pupuk Kandang - Fikrinda Fikrinda (Fakultas Pertanian, Universitas Syiah Kuala, 2007)
Evaluation of Same Biological Properties of Maize Rhizosphere on Tsunamy-Affected Land Caused by Inoculation of Arbuscular Mycorrhizae Fungi (AMF) and ManureABSTRACT. Tsunami caused soil degradation and plant productivity. Inoculation of arbuscule mycorrhizae fungi (AMF) and manure were the methods which are able to improve soil quality. Soil biology properties was a parameter that can be used to assess the quality of a land. The objective of this study were to evaluate some properties of soil biology in the tsunami-affected land influence by AMF and manure. This experiment was conducted to Randomized Block Design with three replications. The results showed that the treatment affecting some soil biology properties was inoculation of AMF. This inoculation had highly significant effect on phosphate solubilizing microorganisms, significant effect on total microbial population, fungi, bacteria, and celulolytic microorganisms, whereas their activity were not affected significantly.